Creative Compositions of the Outstanding Artist from Budzhak Pavel Gutsu: Array - Shevchuk, Tetyana; Ursu, Natalia (Journal of Danubian Studies and Research, 2021)
The article deals with the creative activities of Pavel Gutsu – famous Budzhak artist of Romanian origin, whose works have received the European recognition. The authors analyze the main ideas of his creative compositions, as well as his creative manner.